An Analysis of the Canadian Military-Naval Industry in the Period 2010-2018 - Pires Barbosa Barreto, Jéssica; Santos, Thauan (Revista Brasileira de Estudos de Defesa, 2021)
Canadian military naval industry has historically suffered from cycles of high investment during periods of conflict and cuts in peacetime. After years of scrapping, the government turned to the sector through the initiative of the National Shipbuilding Strategy (2010), which is an ambitious attempt to modernize the navy. Taking this scenario into account, the main purpose of this paper is to understand the role of the State as a promoter of the interactions between the relevant actors and the rules of this industry. To do so, the analysis will be based on the Structure-Conduct-Performance (SCP) paradigm, allowing a better understanding of the dynamics of the industry and a clearer identification of its important variables. Setting up a case study, this research uses official data, documents, reports and academic papers. the time frame covers the period 2010-2018, due to the launch of the Canadian shipbuilding strategy, which is a milestone for the revitalization and operation of the Canadian naval industry. This policy changed the components of the country’s military naval industry.